2020
DOI: 10.1148/radiol.2020191711
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Dynamic Oxygen 17 MRI at 7.0 T for the Cerebral Oxygen Metabolism in Glioma

Abstract: C ancer cells predominantly gain energy through a high rate of glycolysis followed by lactic acid fermentation even in the presence of abundant oxygen (known as the Warburg effect). Consequently, both the higher glucose uptake rate and the reduced cerebral metabolic rate of oxygen (CMRO 2 ) consumption pose possible targets for imaging metabolic tumor activity.Conventional MRI sequences do not provide information on tissue metabolic activity. MR spectroscopy allows for the detection of metabolic products in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…Furthermore, the high metabolic turnover rate of GB requires intensive angiogenesis in order to maintain the high metabolic demand. Our findings with regard to GB oxygen metabolism concur that of previously published studies [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the high metabolic turnover rate of GB requires intensive angiogenesis in order to maintain the high metabolic demand. Our findings with regard to GB oxygen metabolism concur that of previously published studies [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that ISL2 shared a similar oncogenic role as its family member, ISL1, in other cancers [29,30]. Due to its rapid and infiltrating growth properties, glioma shows active metabolism and uses an abundant blood supply in tumor tissues [27,31]. These properties also lead to complete surgical resection and tumor recurrence [32].…”
Section: Discussionmentioning
confidence: 63%
“…Hoffmann et al 232 obtained the first dynamic 17 O MR data in a patient with glioblastoma, showing a decreased CMRO 2 value within the tumor tissue. Recently, a 17 O inhalation study including 10 patients with brain tumors was published 233 in which both high-grade and low-grade gliomas exhibited a lower 17 O MR signal increase in the tumor region and a decrease in tumor CMRO 2 , which is in accordance with the Warburg effect.…”
Section: X-nuclei Magnetic Resonance Spectroscopy and Magnetic Resonance Imagingmentioning
confidence: 85%